2004
DOI: 10.1007/s00261-003-0147-2
|View full text |Cite
|
Sign up to set email alerts
|

MRI of fetal GI tract abnormalities

Abstract: We describe the magnetic resonance (MR) patterns of a variety of fetal gastrointestinal (GI) abnormalities. Thirty-two fetuses between 23 and 38 weeks' gestation with abnormal appearance of the GI tract by ultrasound underwent MR imaging with T1- and T2-weighted sequences. The MR aspect of intestinal atresia (duodenal atresia, one case; small bowel atresia, nine cases) included dilatation of the bowel loops, accurate assessment of the normal bowel distal to the atresia (except in the patient with multiple atre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
1
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(82 citation statements)
references
References 33 publications
4
72
1
5
Order By: Relevance
“…Fetal magnetic resonance imaging (MRI) has evolved over the last few years as a supplementary imaging method for fetuses at risk, with several studies published on the MR appearance of the fetal abdomen and gastrointestinal tract [1][2][3]. However, no systematic study on the MRI appearance of the fetal gallbladder has yet been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Fetal magnetic resonance imaging (MRI) has evolved over the last few years as a supplementary imaging method for fetuses at risk, with several studies published on the MR appearance of the fetal abdomen and gastrointestinal tract [1][2][3]. However, no systematic study on the MRI appearance of the fetal gallbladder has yet been performed.…”
Section: Introductionmentioning
confidence: 99%
“…In the malformation without urorectal fistula, the rectal signal remained normal (1,2). In our case, absence of normal meconium signal was suggesting for an urorectal fistula (1,9). The situation of the cul-de-sac may be interesting to consider.…”
Section: Discussionmentioning
confidence: 69%
“…If the two structures are in close contact, a high ARM would be suspected; if the two structures are separated by a third one, the diagnosis of cloacal malformation is suggested. In the malformation without urorectal fistula, the rectal signal remained normal (1,2). In our case, absence of normal meconium signal was suggesting for an urorectal fistula (1,9).…”
Section: Discussionmentioning
confidence: 76%
“…We performed a literature search via PubMed on this topic (searching until 2005) and found that no-one except Petrikovsky et al 3 has ever quantified human fetal swallowing movements. Various other studies have quantified ovine fetal swallowing 4,5 .…”
Section: Quantification Of Fetal Swallowing By Ultrasound Is Impossiblementioning
confidence: 99%